Diversity and ecology of Pteridophytes in Cendil heath forest and Gurok Beraye tropical rainforest, Belitung Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Priambudi AS, Chikmawati T, Sulistijorini, Fakhrurrozi Y. 2022. Diversity and ecology of Pteridophytes in Cendil heath forest and Gurok Beraye tropical rainforest, Belitung, Indonesia. Biodiversitas 23: 4775-4782. The tropical heath forest is a unique ecosystem type characterized by sandy and acidic soils with poor nutrients and water availability, making this ecosystem very vulnerable to disturbances. Yet, knowledge regarding the diversity and ecology of the biological elements of heath forests is still very limited, moreover, information on lesser-known plant groups, such as pteridophytes. Pteridophytes can be used as indicators of the quality of a forest ecosystem since they are cosmopolitan and have an excellent adaptation to various habitats. Belitung Island, Indonesia, is a region with a large proportion of tropical heath forest and small areas of tropical rainforest. There are only a few studies on comparison of the flora of the two ecosystem types on Belitung Island. This research aimed to compare the diversity and the ecology of pteridophytes that grow in the Cendil heath forest and the Gurok Beraye tropical rainforest, Belitung Island. The study used the cruise and the purposive sampling methods to record all pteridophytes within the sampling plots measuring 5 x 5 m alternately located on the right and left of line transects with a length of 50 meters each transect. Ecological data were calculated using the Important Value Index (IVI), Shannon-Wiener diversity index, Margalef richness index, Evenness index, Sorensen similarity index, Morisita distribution index, and Canonical Correspondence Analysis. The results showed that as many as 31 species of pteridophytes belonged to 14 families in the Cendil heath forest and Gurok Beraye tropical rainforest. The pteridophytes found in the Gurok Beraye tropical rainforest were higher (30 species) than that in the Cendil heath forest (9 species). There was high dominance of a few species in the Cendil heath forest due to the presence of three species with high IVI, namely Dicranopteris linearis, Palhinhaea cernua and Dicranopteris splendida. In contrast, pteridophytes in the Gurok Beraye tropical rainforest were evenly distributed with no high dominance species. Environmental parameters that affected the diversity and abundance of pteridophytes included temperature, light intensity, humidity, and altitude.